Atypical E2Fs: new players in the E2F transcription factor family - Lammens, Tim (2009)
As major regulators of the cell cycle, apoptosis and differentiation, E2F transcription factors have been studied extensively in a broad range of organisms. The recent identification of atypical E2F family members further expands our structural, functional and molecular view of the cellular E2F activity. Unlike other family members, atypical E2Fs have a duplicated DNA-binding domain and control gene expression without heterodimerization with DP proteins. More recently, knock-out strategies in plants and mammals have pinpointed that atypical E2Fs play a critical role in plant cell size control, endocycle regulation, proliferation, and apoptotic response upon DNA stress. Here, we review the emerging biochemical and genetic data on these unique E2F members and discuss their roles in plant and animal development. Their position at the crossroads between proliferation and DNA stress response marks these novel E2F proteins as interesting study objects in the field of tumor biology.